Altered [videorecording (DVD)] - Vuorensola, Timo; Felton, Tom, 1987-; Adams, Aggy K.; Bugulova, Liza; Jijikine, Igor, 1965-; Brake, Richard, 1964- (Well Go USA Entertainment, 2026)
In a dystopian future, genetically enhanced humans dominate society in a life of luxury, while those without struggle in poverty-stricken ghettos. A disabled inventor has a mission to level the playing field and fight against the corrupt and oppressive system. He constructs an armored suit giving him strength and mobility, and risks everything to change the world and protect genetic outcasts, but every revolution has a cost.